The Virgin’s Body and the Sheikh’s Head: Eastern Orthodox and Muslims Living Together (or Not) in Bansko, Strumica area, North Macedonia - Valtchinova, Galia (Fieldwork in Religion, 2024)
The village of Bansko, in the Republic of North Macedonia, is known in historical-ethnological studies for its Muslim heterodox community. The Eastern Orthodox Macedonian community in the village started to gain visibility since the 1950s, to become dominant in the last decades. The village provides a good example of how the dynamics of religious communities living together is revealed through the activities of local religious virtuosi, who interpret and even may influence processes of peaceful or conflictual coexistence. This article is based on fieldwork conducted between 1999 and 2006, primarily focusing on a local female Christian-Orthodox seer whose activities, based on dream revelations, led to a Christian-Orthodox re-interpretation of the local religioscape. The latter consists in a dense network of Christian and Muslim holy places, whose making is evoked through legends and narratives of dreams and visions. Here, the legends around a miracle-working icon of Theotokos believed to be the Virgin’s body, and the disputes over the wooden sculptured head of a sheik that marked the place of his tomb, are used as metaphors to describe the shifting relationship between the two religious communities over time.